2021
DOI: 10.1002/aqc.3625
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative impacts of habitat fragmentation and the environmental factors affecting upstream migration in the threatened sea lamprey, Petromyzon marinus

Abstract: River ecosystems are often fragmented by artificial structures, such as weirs. For anadromous species, these structures can impede access to upstream spawning sites and ultimately lead to severe population declines. This study focused on the freshwater spawning migration of the sea lamprey, Petromyzon marinus, an anadromous species threatened by habitat fragmentation across its native range. To quantify the cumulative impacts of multiple weirs on upstream‐migrating adults, and to explore the environmental fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…was increased during periods of elevated river discharge (Davies et al, 2021). Here, we revealed that across all of the lampreys passing Weir S2, there was a strong bimodal distribution in their passage times, whereby 32% of individuals passed within 24 hr of the first approach but the remainder passed after a median delay of over 2 weeks.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…was increased during periods of elevated river discharge (Davies et al, 2021). Here, we revealed that across all of the lampreys passing Weir S2, there was a strong bimodal distribution in their passage times, whereby 32% of individuals passed within 24 hr of the first approach but the remainder passed after a median delay of over 2 weeks.…”
Section: Discussionmentioning
confidence: 68%
“…Passage time is a key metric for assessing the impact of barriers on upstream migration in fish (Silva et al., 2018), and numerous studies have identified the abiotic, individual, and behavioural factors affecting passage rates at barriers (Castro‐Santos et al., 2017; Goerig et al., 2020; Kirk & Caudill, 2017; Newton et al., 2018). A previous study on these lampreys indicated that their passage over Weir S2 was increased during periods of elevated river discharge (Davies et al., 2021). Here, we revealed that across all of the lampreys passing Weir S2, there was a strong bimodal distribution in their passage times, whereby 32% of individuals passed within 24 hr of the first approach but the remainder passed after a median delay of over 2 weeks.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Given the extensive fragmentation of rivers in Britain (Jones et al, 2019), and indeed in Europe (Belletti et al, 2020) and the world more generally (Grill et al, 2019), future work should consider incorporating barriers into network configurations, especially as these barriers can affect the behaviour of freshwater organisms (Rodeles et al, 2021;Starrs et al, 2017). However, this would require an additional algorithm relating to barrier permeability, such as the ability of fish to move upstream according to river level (Davies et al, 2021), and whether the barrier incorporated a fish by-pass structure (Pereira et al, 2017). Interactions of the invading fish with the native community were also not considered within the model, and it is acknowledged that these interactions can be an important factor in the outcome of biological invasions where, for example, the extent of native biotic resistance and resilience to the invader can determine the extent of its establishment and spread (Alofs & Jackson, 2014;Svenning et al, 2014;Thompson & Fronhofer, 2019).…”
Section: Discussionmentioning
confidence: 99%